Characteristics and expression of lncRNA and transposable elements in Drosophila aneuploidy. - Zhang, S.; Wang, R.; Zhu, X.; Zhang, L.; Liu, X.; Sun, L. (iScience, 2023)
Aneuploidy can globally affect the expression of the whole genome, which is detrimental to organisms. Dosage-sensitive regulators usually have multiple intermolecular interactions, and changes in their stoichiometry are responsible for the dysregulation of the regulatory network. Currently, studies on noncoding genes in aneuploidy are relatively rare. We studied the characteristics and expression profiles of long noncoding RNAs (lncRNAs) and transposable elements (TEs) in aneuploid Drosophila. It is found that lncRNAs and TEs are affected by genomic imbalance and appear to be more sensitive to an inverse dosage effect than mRNAs. Several dosage-sensitive lncRNAs and TEs were detected for their expression patterns during embryogenesis, and their biological functions in the ovary and testes were investigated using tissue-specific RNAi. This study advances our understanding of the noncoding sequences in imbalanced genomes and provides a novel perspective for the study of aneuploidy-related human diseases such as cancer.